Molecular characterization and agronomic trait analysis of rice Os09g24220 gene insertion mutants - Yuan Bing; Cui Hairui; Fu Haowei; Jiang Meng; Li Ruiqing; Zhao Haijun; Shu Qingyao (浙江大学学报. 农业与生命科学版)
The mismatch repair (MMR) is a major pathway in DNA repair system, which is critical for maintaining genome stability and DNA replication fidelity, as it is responsible for the recognizing and repairing erroneous insertions, deletions and mismatch of bases newly arising during DNA replication and genetic recombination, as well as during the repair of some forms of DNA damage. The major components in the MMR system include MutS, MutH, and MutL in Escherichia coli. In eukaryotes, homologues of MutS and MutL have been found, but not of MutH. Based on homology, several MutS homologues have also been identified and cloned from Arabidopsis thaliana. Amongst these homlogues MSH2 complexes with MSH6, MSH3 or MSH7 form MutSα, MutSβ and MutSγ heterodimers to recognize different types of mutations, respectively. Mutation or disruption of MMR gene causes significantly increased frequencies of point mutations and microsatellite instability, thus to enhance genetic diversity for plant breeding.Rice is an important food crop and a prominent molecular model species for monocotyledonous plants. Some MMR genes have been annotated in Rice Annotation Project Database, one of which is Os09g24220, a homologue to Msh6 (At4g02070) in the MMR system of A. thaliana. However, no information is available for the Os09g24220 gene function and its mutator phenotype in rice. We reasoned that, if the disrupted Os09g24220 gene can enhance genetic diversity, offspring exhibiting mutations in agronomic traits could be generated using this approach. Herein, we mainly conducted molecular characterization of Tos17 insertion mutants of the Os09g24220 gene and analyzed their agronomic traits, to provide a foundation for the function studies of the Os09g24220 gene and exploitation of the mutant in rice mutation breeding.Three insertion mutants, NF9010, NF7784 and ND6011 with the Tos17 insertion at the 1st, 8th exons and 3′- UTR (untranslated region), respectively, were characterized by triple-primer PCR and RT-PCR. The Tos17 insertion in Os09g24220 gene was confirmed and all three insertion mutants were homozygous. In both NF9010 and NF7784 mutant seedlings, partial Os09g24220 mRNA transcripts were detected with the primer sets that amplified upstream region of the insertion site, but it was not detectable with the primer sets at the downstream region or across the insertion site, indicating that NF9010 and NF7784 lack full-length, functional Os09g24220 mRNA despite the existence of truncated transcripts. However, all Os09g24220 transcripts were detected with primer sets that amplified the upstream, internal and downstream fragments of whole functional region in ND6011 mutant, but no transcript was detected with the primer set across the insertion site, suggesting that ND6011 has the functional mRNA, but not full-length mRNA. Agronomic traits, such as plant height, number of productive panicles, panicle length, seed-setting rate and mass of 1 000 grains, of the insertion mutants were checked and compared with those of their wild type, Nipponbare. Results indicated that at least one trait for each mutant changed significantly. The mutant ND6011 just showed significantly (P<0.05) decreased seed-setting rate, but both NF7784 and NF9010 displayed significant (P<0.01) reduction in ear length and seed-setting rate, moreover plant height of NF9010 was also significantly lowered (P<0.05).In conclusion, some agronomic traits of Tos17 insertion mutants of the Os09g24220 gene changed significantly in rice plants, showing the mutator phenotype. Furthermore, different insertion mutants displayed different mutator phenotypes, which are related to effects on Os09g24220 gene function of different Tos17 insertion sites. These findings provide foundations for investigating the function of the Os09g24220 gene in DNA repair and exploiting such mutants in induced mutation breeding in rice.